Potassium iodide reduces the stability of triple-cation perovskite solar cells. Issue 66 (6th November 2020) - Alanazi, Tarek I.; Game, Onkar S.; Smith, Joel A.; Kilbride, Rachel C.; Greenland, Claire; Jayaprakash, Rahul; Georgiou, Kyriacos; Terrill, Nicholas J.; Lidzey, David G.
Abstract : The addition of alkali metal halides to hybrid perovskite materials can significantly impact their crystallisation and hence their performance when used in solar cell devices. Abstract : The addition of alkali metal halides to hybrid perovskite materials can significantly impact their crystallisation and hence their performance when used in solar cell devices. Previous work on the use of potassium iodide (KI) in active layers to passivate defects in triple-cation mixed-halide perovskites has been shown to enhance their luminescence efficiency and reduce current–voltage hysteresis. However, the operational stability of KI passivated perovskite solar cells under ambient conditions remains largely unexplored. By investigating perovskite solar cell performance with SnO2 or TiO2 electron transport layers (ETL), we propose that defect passivation using KI is highly sensitive to the composition of the perovskite–ETL interface. We reconfirm findings from previous reports that KI preferentially interacts with bromide ions in mixed-halide perovskites, and – at concentrations >5 mol% in the precursor solution – modifies the primary absorber composition as well as leading to the phase segregation of an undesirable secondary non-perovskite phase (KBr) at high KI concentration. Importantly, by studying both material and device stability under continuous illumination and bias under ambient/high-humidity conditions, we show that this secondary phase becomes a favourable degradation product, and that devices incorporating KI have reduced stability.